2016
DOI: 10.1002/jts.22081
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Trauma and Adverse Health and Occupational Outcomes Among Men Serving in the U.S. Military

Abstract: Although absolute counts of U.S. service men who experience sexual trauma are comparable to service women, little is known about the impact of sexual trauma on men. The association of recent sexual trauma (last 3 years) with health and occupational outcomes was investigated using longitudinal data (2004-2013) from the Millennium Cohort Study. Of 37,711 service men, 391 (1.0%) reported recent sexual harassment and 76 (0.2%) sexual assault. In multivariable models, sexual harassment or assault, respectively, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
(38 reference statements)
2
37
0
Order By: Relevance
“…We did not find an association between reported history of sexual trauma and persistent PTSD in adjusted models, though there was an association in unadjusted models. Sexual assault has been shown to be one of the most significant types of traumatic events in predicting PTSD and other mental health outcomes [ 50 , 51 ]. In our analysis, the null association with sexual assault may be attributable to the small number of sexual assault cases or high correlation with other statistically significant variables such as physical assault.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find an association between reported history of sexual trauma and persistent PTSD in adjusted models, though there was an association in unadjusted models. Sexual assault has been shown to be one of the most significant types of traumatic events in predicting PTSD and other mental health outcomes [ 50 , 51 ]. In our analysis, the null association with sexual assault may be attributable to the small number of sexual assault cases or high correlation with other statistically significant variables such as physical assault.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were included based on factors associated with PTSD and MDD identified in prior research [17, 3538].…”
Section: Methodsmentioning
confidence: 99%
“…Because the items do not ask whether the sexual trauma occurred while in the military we restricted the sample to those who were in the military when they submitted their questionnaire, ensuring that the participant was in the military for the full 3‐year period that was reported on. Consistent with previous Millennium Cohort studies (Millegan et al., ; Millegan, Wang, LeardMann, Miletich, & Street,2016), responses to these items were coded as a 3‐level variable: no report of sexual harassment or sexual assault (referent group), report of sexual harassment only, and report of sexual assault with or without sexual harassment. Sexual trauma was measured at study baseline, but was allowed to vary over the study time when additional follow‐up was available; however, once someone indicated that he or she had experienced a sexual trauma, that exposure carried forward.…”
Section: Methodsmentioning
confidence: 99%